General practitioners adherence to recommendations from geriatric assessments made during teleconsultations for the elderly living in nursing homes. Issue 2 (October 2015) - Georgeton, E.; Aubert, L.; Pierrard, N.; Gaborieau, G.; Berrut, G.; de Decker, L.
Highlights Telemedicine is an innovative care for the elderly living in nursing homes. We examine factors associated with adherence to recommendations from geriatric assessments made during teleconsultations. Adherence to recommendations was highly satisfactory. Adherence to recommendations made during the teleconsultation is associated with the depressive syndrome's existence and the expert medical advice recommendations.